Catalogue of the types of Diptera, Hemiptera, Hymenoptera, Odonata, and Strepsiptera in the IEXA Entomological Collection at Instituto de Ecología, A. C. - Vega-Badillo, Viridiana; Hernández-Ortiz, Vicente; Valenzuela-González, Jorge E.; Novelo-Gutiérrez, Rodolfo; Ibáñez-Bernal, Sergio; Reynoso-Velasco, Daniel (Zootaxa, 2024)
The IEXA Entomological Collection at Instituto de Ecología, A. C. (Xalapa, Veracruz, Mexico) is one of the most important scientific collections in Mexico based on its taxonomic and geographic coverage and number of specimens (approx. 400,000), including its name-bearing types. The insect orders best represented in the collection are Coleoptera, Diptera, Hemiptera, Hymenoptera, and Odonata. The present catalogue is the result of a recent update of the collection database, which included capturing the number, sex, and label data on specimens in the types collection. This publication is the first part of the catalogue and includes information on five orders (Diptera, Hemiptera, Hymenoptera, Odonata, and Strepsiptera), 28 families, 84 genera, and 175 species. In total, the IEXA collection has 1,532 type specimens of these five orders, of which 77 are holotypes and 1,455 paratypes (including eight allotypes). According to the original descriptions, type specimens of two species in Hemiptera were to be deposited in the IEXA; however, the specimens are not in the collection and are considered to be lost.